PEMBELAJARAN DIGITAL STORYTELLING DALAM KONTEN MEDIA SOSIAL UNTUK GENERASI MUDA - Lydia Irena; Eldiani Febyola; Michelle Augustine; Alexandra Carolina (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2025)
Indonesian teenagers currently dominate internet and social media users, with penetration rates nearly equal: 97.17% in the 19–34 age group and 99.16% in the 13–18 age group. The most frequently accessed apps include Tiktok, YouTube, Whatsapp, Instagram, and Facebook, with Tiktok leading the way in terms of monthly usage duration. Social media now serves not only as a means of communication but also as a Platform for self-expression, entertainment, and a space for creating economic opportunities. The development of social media has made the younger generation both users and producers of digital content. However, many of them do not yet understand the importance of storytelling in creating inspiring, educational, and character-building content. As a result, the content produced is often instantaneous, shallow, and even has the potential to have negative impacts. Various studies confirm that the application of digital storytelling can improve message quality, deepen communication meaning, build a positive image of the younger generation, and strengthen digital literacy. Through the integration of text, audio, visuals, and video, digital storytelling has been shown to foster learning motivation, collaboration skills, and critical and creative thinking skills. Furthermore, authentic narratives that are close to the audience's experiences strengthen trust, create emotional bonds, and help teenagers explore their identity. At the same time, SMA Santa Maria 1 Cirebon's partner also experienced limited technical skills in content production with digital storytelling and expert guidance. Therefore, the solution offered is a Student Creativity Program (PKM) titled